TEACHER MANAGEMENT OF INTEGRATED ISLAMIC ELEMENTARY SCHOOL IN BENGKULU PROVINCE - Citra Dewi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Integrated Islamic elementary school is one of alternative educational institution and main choice of the society in disruption era. Meanwhile Integrated Islamict elementary school not only teach about cognitive lessons only but also combining  moral values with charge material and application in all daily activities in their school . Teacher becomes the main central in learning  activities at integrated Islamic elementary school. The goals of this research to know and to analyze   activities some aspects; (1) planning; (2) organizing; (3) implementation; (4) supervision, and (5) evaluation. The Method that used in this research is qualitative by using  technique   interviews, observations, and documentation. The results stated that (1) the planning was formed team formulation teacher recruitment, socialization, teacher test competence, and made the decision of the teacher chosen,(2)  the activities that in organizing step was coordinating on the associated unit in school in guidance of new teachers, (3) Activities in implementation form training basic for teachers, internships , workshops, and training, (4) the activities of supervision conducted in the form of monitoring of learning through supervision learning in class , supervision of instructional tools, and (5) the activities in evaluation step were performance and evaluation learning that shows results corresponding with expected criteria although still found teachers who are not productive in writing creation scientific aspect.